Prevalence, Virulence Regulation, and Resistance Mechanisms of Clinical Staphylococcus aureus Isolates: The Role of the agr System and Mobile Genetic Elements in Al-Diwaniyah, Iraq - Hanaa Neamah Abdullah; Nada Ahmed Fairooz; Bushra Hamad Obaid; Sura A Al-Ganahi; Robeena Farzand (Journal of Biomedicine and Biochemistry, 2026)
Background: Infections by Staphylococcus aureus are continued as a real issue especially in hospital-acquired disease. It can produce virulent factors that can be controlled by the accessory gene regulator (agr), and it can be affected by mobile genetic elements (MGEs). It should be known their mechanism in local isolates as it is crucial for monitoring infections and treatment approaches.Objectives: To evaluate S. aureus prevalence in clinical samples and to discover the consequence of the agr system and MGEs in regulating virulence.Methods: Microbiological procedures were used to gather clinical samples. Also, molecular assays were accomplished to determine agr types, key virulence-associated genes, and MGEs. The data of this study was evaluated to estimate the association among agr function, virulence gene distribution, and resistance traits.Results: Most clinical samples contain active agr system, with major of agr group I. Virulence factors like enterotoxins, hemolysins, and adhesion-associated genes were extensively spread. MGEs such as pathogenic islands and plasmids were detected and cause antimicrobial resistance and virulence expression. Interestingly, in the isolated samples, active agr systems present a significant association with toxin production more than those with dysfunctional variants.Conclusion: S. aureus samples show high dominance and genetic variant. Virulence measurements are strongly affected by the agr system and MGEs. Molecular monitoring is important step to display these influences and support active therapeutic and infection-control measures.